Views Of The MUI, NU, And Muhammadiyah On The Expansion Of The Meaning Of Ashnâf Fî Sabîlillâh In Indonesia - Nur Sillaturohmah Handayani; Isman; Muthoifin (al-Afkar, Journal For Islamic Studies, 2023)
This research aims to analyze the views of the three largest Islamic organizations in Indonesia, namely the Indonesian Ulema Council (MUI), Nahdlatul Ulama (NU), and Muhammadiyah, related to the expansion of the meaning of ashnâf fî sabîlillâh in the current era. This research uses descriptive analytic qualitative method by collecting data from various related sources. The results showed that the Indonesian Ulema Council (MUI), as a joint community organization of various Islamic mass organizations in Indonesia, has an important role in providing fatwas and becoming a reference for Muslims and the government. MUI also has a view related to the expansion of the meaning of Ashnâf Fî sabîlillâh. Nahdlatul Ulama (NU) through the NU Institute of Zakat and Infaq Shodaqoh (LAZISNU) views that ASNAFIS has a general meaning, namely for the defense of Islam, Muslims, and public interests such as establishing schools and hospitals. Muhammadiyah through the Muhammadiyah Zakat and Infaq Shodaqoh Institute (LAZISMU) interprets ASNAFIS in three categories. First, the meaning of war, defense, and Islamic security. Second, the meaning of Islamic religious interests. Third, the meaning of Islamic religious interest. This research is expected to contribute to enriching the understanding of the views of three major mass organizations on the expansion of the meaning of ASNAFIS. In addition, this research also emphasizes the importance of Islamic legal certainty related to zakat in the context of zakat management which is increasingly growing in Indonesia along with the rapid development of zakat payment technology.